FUNGSI AUDIT INTERNAL DALAM MENDETEKSI KECURANGAN PADA INSPEKTORAT PROVINSI SUMATERA SELATAN - Fakih, Firdaus; Rakhmat, Rakhmat; Yuliana, Yuliana; Yudisiana, Prima Aulia; Yusro, Yusro (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2024)
This research purposed to know the role of internal audit in the detecting fraud in Government of South Sumatera. Data were collected by depth- interviews with auditors and officials in Inspektorat of South Sumatera. Results of data collection were analyzed of using qualitative method with interpretive approach. The results showed that the government's internal audit of Inspektorat South Sumatera has a role in detecting fraud begins with the provision of mentoring (coaching), supervision and regular inspection or perpetually in a particular examination.